2018
DOI: 10.24191/srj2018.15.1.17-29
|View full text |Cite
|
Sign up to set email alerts
|

Bending Strength of Steel Fibre Reinforced Concrete Ribbed Slab Panel

Abstract: Nowadays, demands in the application of fibre in concrete increase gradually as an engineering material. Rapid cost increment of material causes the increase in demand of new technology that provides safe, efficient and economical design for the present and future application. The introduction ofribbed slab reduces concrete materials and thusthe cost, but the strength of the structure also reduces due to the reducing of material. Steel fibre reinforced concrete (SFRC) has the ability to maintain a part of its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The results also revealed that there was no damage at the interface between the pre-cast unit and the topping concrete, and that the composite specimens behaved like full composites. Steel fiber as the main reinforcements in reinforced concrete (SFRC) was also explored by others [9,10]. Both studies on the flexural performance of ribbed slab by considering normal strength concrete (fck = 30 N/mm 2 ) reinforced with 0.5% (40 kg/m 3 ) volume fraction of steel fibers.…”
Section: Overview Of Research In Ribbed Slabmentioning
confidence: 99%
See 3 more Smart Citations
“…The results also revealed that there was no damage at the interface between the pre-cast unit and the topping concrete, and that the composite specimens behaved like full composites. Steel fiber as the main reinforcements in reinforced concrete (SFRC) was also explored by others [9,10]. Both studies on the flexural performance of ribbed slab by considering normal strength concrete (fck = 30 N/mm 2 ) reinforced with 0.5% (40 kg/m 3 ) volume fraction of steel fibers.…”
Section: Overview Of Research In Ribbed Slabmentioning
confidence: 99%
“…Both studies on the flexural performance of ribbed slab by considering normal strength concrete (fck = 30 N/mm 2 ) reinforced with 0.5% (40 kg/m 3 ) volume fraction of steel fibers. The respective investigation studied on varying the topping flange thickness [18] and considered different numbers of ribs [10]. These studies demonstrated promising performance of the SFRC ribbed slab under bending.…”
Section: Overview Of Research In Ribbed Slabmentioning
confidence: 99%
See 2 more Smart Citations
“…According to clause 3.6.1.3 of BS8110-Part 1 (British Standards Institution, 2004), the rib spacing should not exceed 1.5m centre to centre, and the rib height should not exceed four times the rib width. Samsudin et al (2018) studied two and three-ribbed SFRC slabs. The outcome indicates that the maximum load capacity of a two-ribbed slab is greater than that of a three-ribbed slab, thus a higher strength capacity.…”
Section: Introductionmentioning
confidence: 99%